Interpersonal Reactivity Index: Cultural adaptation and psychometric analysis in undergraduate Colombian students - Chaparro, Reynel; Pineda-Roa, Carlos Alejandro (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
A cultural validation of the Interpersonal Reactivity Inventory (IRI) was carried out, translating into Spanish and reviewing its psychometrical properties, evaluating two-factor, four-factor and four-factor + one general-factor models. 386 university students participated in a non-probabilistic sampling (18 - 30 years old, M=20.2; SD=2.6). The reliability of the dimensions was adequate (Cronbach's alpha 0.66 <α <0.78; McDonald's Omega 0.70 <Ω <0.80). Confirmatory Factor Analysis showed good fit to four-factor model and for four-factor + one general-factor model and insufficient in two-factor model. Women showed higher scores in affective dimensions whereas men showed higher scores in cognitive dimensions. IRI 22 items reduced version shows good psychometric properties in young Colombian population.